2023
DOI: 10.1136/bmjopen-2022-069083
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioecological factors and electronic cigarette use among Thai youth: an institution-based cross-sectional study

Acharaporn Seeherunwong,
Mathuros Tipayamongkholgul,
Suleemas Angsukiattitavorn
et al.

Abstract: ObjectivesThis study aimed to examine cigarette use distribution, pattern of e-cigarette use and to determine socioecological model (SEM) factors associated with e-cigarette use among Thai youth (aged 15–24).DesignAn institution-based cross-sectional study.ParticipantsThe study conducted in five regions: the north, south, central, northeast and Bangkok area of Thailand from May to October 2021. An internet-based, self-administered questionnaire was developed based on the SEM. We enrolled 13 139 students who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…E-cigarette use showed significant correlations with having a smoking friend, and also with having a smoking mother. These findings are in line with a study conducted among young adults in Thailand, revealing that having a partner using e-cigarettes increased the likelihood of e-cigarette use by 3.239 times [ 48 ]. Similarly, a study involving university students in Qatar reported consistent results regarding factors associated with using e-cigarettes and water pipes [ 9 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…E-cigarette use showed significant correlations with having a smoking friend, and also with having a smoking mother. These findings are in line with a study conducted among young adults in Thailand, revealing that having a partner using e-cigarettes increased the likelihood of e-cigarette use by 3.239 times [ 48 ]. Similarly, a study involving university students in Qatar reported consistent results regarding factors associated with using e-cigarettes and water pipes [ 9 , 49 ].…”
Section: Discussionsupporting
confidence: 91%